Influence of cathode gas diffusion media on the performance of the PEMFCs - Prasanna, M; Ha, HY; Cho, EA; Hong, SA; Oh, IH (ELSEVIER SCIENCE BV, 2004)
The influence of gas diffusion media (GDM), i.e. carbon paper, on PEMFCs was studied. The study was based on GDM thickness pore size distribution, air-permeability, electronic resistance and hydrophobicity. Cell performances were correlated with the physical properties of the GDM and reasonable agreements were made based on the oxygen-gain which was regarded as an index of mass transfer in the cathode when the reactant was changed from neat oxygen to air. The results show that gas permeability and pore size diameter of the GDM are the important factors in the performance of the cell compared to all other physical properties. When the mean pore size diameter is in the range of about 25-40 mum, thickness of the GDM and its gas permeability play crucial role in lowering oxygen-gain. GDM with larger pore size shows severe flooding in cathodes compared to GDM with smaller pore diameter. Optimized Teflon content in the GDM was found to be 20% whereas above this content gas permeability of the GDM decreased substantially due to decreased porosity. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: FUEL-CELLS; MODEL